Gendered practices in veterinary organisations. (5th October 2019) - Knights, David; Clarke, Caroline
Abstract : As a result of scandals concerning sexual harassment in Hollywood and in the media, as well as questions regarding the size of the gender pay gap, considerable attention has recently been paid to questions of gender diversity and discrimination in organisations. Gender issues would appear particularly salient within the veterinary profession, not least because women are beginning to outnumber men as practitioners. While this research on veterinary surgeons was not initially focused on gender, as the study progressed gender became an issue of such importance that it could not be ignored. Although 'feminized in numerical terms', the veterinary profession and 'its professional structure and culture remains gendered masculine'. Translated into practice, this means that although 76 per cent of vet school graduates are currently female, disproportionately few have risen or are rising through the hierarchy. On the surface it is easy to rationalise this away partly by simply stating how many female vets appear to sacrifice career for family, but the authors' aim is to go beyond merely repeating and reinforcing the common sense view of female reproduction and parenting as the sole explanation for gender inequality within this and other professions.